2021
DOI: 10.31234/osf.io/m59nb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotional salience modulates the forward flow of memory

Abstract: Conditional response probability (CRP) analyses applied to free recall data indicate that recall occurs for contiguous items with forward-directionality, thought to reflect the shared encoding context of nearby items. We hypothesized that a context disruption, produced by presenting infrequent oddballs, would modulate CRP curves, increasing the forward-flow of recall due to strong binding of items presented after these oddballs to the new encoding context. Seventy young, healthy male and female participants en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…Individuals likely used semantic information to guide recall in our Studies, but we nevertheless observed consistent and reliable temporal structure in recall as well: every Study showed a robust temporal contiguity effect in recall. This is in line with prior work demonstrating that, while many variables -such as list length, presentation times, incidental vs. intentional encoding, emotional salience, and interitem distraction -can influence the the magnitude of the temporal contiguity effect, it tends to be reliably present (Healey et al, 2019;Dester et al, 2020;Lazarus et al, 2020;Peris-Yague et al, 2021).…”
Section: Exploring Reasons For the Null Effect Of Attentional States ...supporting
confidence: 90%
“…Individuals likely used semantic information to guide recall in our Studies, but we nevertheless observed consistent and reliable temporal structure in recall as well: every Study showed a robust temporal contiguity effect in recall. This is in line with prior work demonstrating that, while many variables -such as list length, presentation times, incidental vs. intentional encoding, emotional salience, and interitem distraction -can influence the the magnitude of the temporal contiguity effect, it tends to be reliably present (Healey et al, 2019;Dester et al, 2020;Lazarus et al, 2020;Peris-Yague et al, 2021).…”
Section: Exploring Reasons For the Null Effect Of Attentional States ...supporting
confidence: 90%